E-learning in postgraduate urology training: a Covid-19 pandemic experience - Hussain, Mudassir; Abdul Khalique; Pardeep Kumar; Asad Shehzad Hassan; Altaf Hashmi; Adeeb Ul Hassan Rizvi (Journal of the Pakistan Medical Association, 2022)
Since the declaration of a COVID-19 pandemic in March 2020 teaching institutions started the process of adjusting to the new challenge. Medical education could not be imparted the way it used to be and some new methods had to be taken to adapt to the pandemic. At our institute, each week two lectures were recorded and later uploaded on the Youtube Channel and shared with students. This was followed by an MCQs based test using Google forms. Ten lectures were delivered in 5 weeks to 55 participants. Majority of residents agreed that this activity increased their knowledge of the subject and opted to continue it in future. With help of short online lectures (< 30 mins) and short online tests (5 MCQs), the learning experience of residents can be enhanced. In future, more online resources can be used to incorporate this method of teaching.